Endoplasmic reticulum-through-Golgi transport assay based on O-glycosylation of native glycophorin in permeabilized erythroleukemia cells: role for Gi3. - Wilson, B S (1993)
An assay for endoplasmic reticulum (ER)-through-Golgi transport has been developed in streptolysin O-permeabilized murine erythroleukemia (MEL) cells. The reporter proteins are metabolically labeled native murine glycophorins, which display a distinctive shift in electrophoretic mobility after acquisition of O-linked oligosaccharides. The O-linked sugars are acquired at a site distal to a brefeldin A block, presumably in a cis Golgi compartment, and sialylation occurs in middle and/or trans Golgi compartments. In permeabilized cells supplemented with cytosolic proteins and an ATP-generating system, 20-50% of the radiolabeled precursor glycophorins can be converted to the mature, sialylated form. This maturation process is ATP- and cytosol-dependent and is blocked by guanosine 5'-[gamma-thio]triphosphate (GTP[gamma S]). Electron microscopy of permeabilized MEL cells shows retention of ER elements, stacked Golgi cisternae, free polysomes, and other subcellular components. In the presence of GTP[gamma S], dilated vesicles accumulate around the Golgi stacks. Antisera to the carboxyl terminus of the Golgi resident alpha subunit of Gi3 inhibit maturation of glycophorin. To our knowledge, a transport assay utilizing O-glycosylation of an endogenous protein as a monitor of ER-through-Golgi traffic in permeabilized cells has not been reported previously. Furthermore, the data provide evidence for heterotrimeric GTP-binding protein involvement in Golgi function.